Firework-related blast injury to the hand and treatment algorithm - Mohan, A; Nolan, GS; Jain, A (BMJ Publishing Group, 2019)
Firework injuries, which most commonly affect hands, are increasing in frequency and severity. We present a pictorial case of a devastating hand injury following a firework explosion in a young male patient. The blast resulted in splaying of the hand with multiple fractures, neurovascular compromise and soft tissue loss. Reconstruction involved a third-ray amputation, fracture fixation, nerve and soft tissue repair resulting in an adequate hand with near-normal appearance. Firework-related hand injuries pose a significant surgical challenge due to the combination of burn and blast forces that can compromise the function of intact vessels and nerves making salvage and reconstruction particularly difficult. Here, we propose a treatment algorithm based on current literature. Our case demonstrates, what initially appeared to be an unsalvageable injury can be reconstructed to produce a functional hand if appropriate surgical measures are taken.